History of contact and age as determinants of rubella among children in Badung District year 2012 - I Ketut Subrata; Anak Agung Sagung Sawitri; Dewa Nyoman Wirawan (Public Health and Preventive Medicine Archive, 2013)
Rubella remains as a health concern in Bali. There have been seven times rubella outbreaks in the last two years, three of which occurred in Badung. No previous research exploring risk factors of rubella have been conducted in Bali. This case control study aimed to obtain the description of risk factors contributing to the incidence of rubella among children in Badung. Total samples were 69 cases and 138 controls. Data were collected by document analysis, interviews, observation and measurements. The instruments used are questionnaires, digital scales brand AND, multifunctional height gauge and meter. Data were analysed using univariate, bivariate and multivariate (logistic regression) methods. The majority of subjects were school-age 170 (82.1%), in a good nutrition status 193 (93.2%), non-immunised 197 (95.2%) and never had contact with the patient 118 (57%). The socioeconomic status is 172 (83.1%) above the regional minimum wage, 77 (37.2%) as private sector employees and 153 (86%) were highly educated. There were four variables found to increase risk of contracting rubella: children age OR=7.19 [95%CI: 2.12-24.36], contact history OR=45.23 [95%CI: 17.67-115.77], residential density OR=2.9 [95%CI: 1.31-6.46] and ventilation OR=3.34 [95%CI: 1.67-6.68]. In the multivariate analysis, contact history OR=44.09 [95%CI: 16.51-117.74] and age OR=16.83 [95%CI: 3.46-18.84] are two dominant factors contributing to rubella among children. Health promotion related to prevention and control, research with accurate diagnosis for control and considering rubella vaccination as a national program need to be conducted.